Glycaemia and body weight are regulated by sodium-glucose cotransporter 1 (SGLT1) expression via O-GlcNAcylation in the intestine - Nishimura, Kimihiro; Fujita, Yukihiro; Ida, Shogo; Yanagimachi, Tsuyoshi; Ohashi, Natsuko; Nishi, Kiyoto; Nishida, Atsushi; Iwasaki, Yasumasa; Morino, Katsutaro; Ugi, Satoshi; Nishi, Eiichiro; Andoh, Akira; et al. (Molecular metabolism (Germany), 2022)
The intestine is an important organ for nutrient metabolism via absorption and endocrine systems. Nutrients regulate O-GlcNAcylation, a post-translational modification of various proteins by O-GlcNAc transferase (OGT). We have previously shown that general OGT knockout induced severe weight loss and hypoglycaemia in mice, but little is known about how O-GlcNAcylation in the intestine modulates nutrient metabolism, especially glucose metabolism, through absorption. We aimed to reveal the roles of O-GlcNAcylation in glucose absorption by the small intestine and elucidate the mechanism by which O-GlcNAcylation regulates sodium-glucose cotransporter 1 (SGLT1) expression. First, we fasted normal mice and examined the changes in glucose transporters and O-GlcNAcylation in the intestine. Then, we generated two lines of small intestine-specific OGT-deficient mice (congenital: Ogt-VKO, tamoxifen-inducible: Ogt-iVKO) and observed the changes in body weight and in glucose and lipid metabolism. Finally, we investigated Sglt1 gene regulation by O-GlcNAcylation using enteroendocrine STC-1 cells. Fasting decreased O-GlcNAcylation in the intestinal epithelium of normal mice. The Ogt-VKO mice showed significantly lower non-fasted blood glucose levels and were underweight compared with litter matched controls. Glycaemic excursion in the Ogt-VKO mice was significantly lower during the oral glucose tolerance test but comparable during the intraperitoneal glucose tolerance test. Furthermore, the Ogt-VKO mice exhibited lower Sglt1 expression in the small intestine compared with the control mice. We obtained similar results using the Ogt-iVKO mice only after tamoxifen administration. The oral d-xylose administration test revealed that the intestinal sugar absorption was diminished in the Ogt-iVKO mice and that GLP-1 secretion did not sufficiently increase after glucose gavage in the Ogt-iVKO mice. When using STC-1 cells, O-GlcNAcylation increased Sglt1 mRNA via a PKA/CREB-dependent pathway. Collectively, loss of O-GlcNAcylation in the intestine reduced glucose absorption via suppression of SGLT1 expression; this may lead to new treatments for malabsorption, obesity and diabetes. [Display omitted] •Intestine-specific OGT depletion results in weight loss and hypoglycaemia.•It reduces SGLT1 expression, resulting in glucose absorption from the gut.•OGT knockdown may contribute to diminish glucose-induced incretin secretion.•OGT may regulate SGLT1 expression via the cAMP/CREB-dependent pathway.•O-GlcNAcylation regulates SGLT1 expression in the intestine and the kidney.